Total hepatectomy and liver transplantation as two-stage procedure. - Ringe, B (1993)
OBJECTIVE: This article describes the experience with a bridging procedure for a prolonged anhepatic period during clinical liver transplantation in case of special emergency situations. SUMMARY BACKGROUND DATA: Hepatic necrosis due to fulminant hepatitis or acute graft failure, as well as severe liver trauma are well-known and accepted indications for urgent liver transplantation. Prerequisite is the allocation of a suitable donor organ. If no allograft is available in time, patients with "toxic liver syndrome" or exsanguinating hemorrhage have been shown to benefit from advanced total hepatectomy. METHODS: As a modification of the standard one-stage procedure, recipient hepatectomy and subsequent liver transplantation are performed in two separate operations. To bridge the prolonged anhepatic period and to allow decompression and return of venous blood, an end-to-side portocaval shunt is constructed temporarily. RESULTS: Thirteen of thirty-two patients underwent hepatectomy but not transplantation subsequently, and died within 34 hours after progressive deterioration. In 19 of 32 patients, transplantation was realized 6-41 hours after hepatectomy; 9 of 19 patients died, mostly from sepsis. Ten of nineteen liver recipients survived the procedure including three unrelated late deaths; presently, seven patients are alive with a follow-up of 3 to 46 months. CONCLUSIONS: Two-stage total hepatectomy with temporary portocaval shunt, and subsequent liver transplantation can be a life-saving approach in patients most likely to die of the sequelae of advanced liver or graft necrosis or exsanguination that cannot be controlled by conventional treatment or immediate liver transplantation.